Assessing Indonesia's Readiness to Integrate Water Accounting into Green Fiscal Policy - Amrie Firmansyah (APSSAI ACCOUNTING REVIEW, 2025)
Research aims: This study aims to map the readiness for integrating water accounting into Indonesia's green fiscal governance by developing a conceptual framework that links water accounting data, public fiscal systems, and the effectiveness of environmental expenditure as the foundation for designing an environmental budget tagging model. Design/Methodology/Approach: The study employs a scoping review approach, synthesizing national and international policy documents related to water management, sustainability reporting, and fiscal governance. Research findings: The study finds that Indonesia has achieved conceptual, regulatory, fiscal, and institutional readiness to adopt water accounting within its green fiscal governance system. The existing statistical infrastructure aligns with the principles of environmental-economic accounting, while the Climate Budget Tagging mechanism provides a fiscal foundation that can evolve into a comprehensive Environmental Budget Tagging system encompassing water-related expenditures. Theoretical contribution/Originality: This study extends the literature by explicitly connecting water accounting with fiscal policy mechanisms, integrating perspectives from environmental–economic accounting, climate governance, sustainability reporting, and public sector accounting into a single conceptual framework applicable to policy design. Practitioner/Policy implication: The findings provide a foundation for policymakers to integrate water-related data into fiscal decision-making, promoting transparent and evidence-based environmental budgeting. Embedding water accounting within fiscal systems can strengthen the efficiency, accountability, and sustainability of public spending, aligning it with national green development goals. Research Limitation/Implication: The study is conceptual in nature and limited to publicly available documents; future research may conduct empirical assessments to validate fiscal-environmental linkages and measure the effectiveness of implementation.